Effects of Dehydration on Brain Functioning: A Life-Span Perspective - Pross, Nathalie (Annals of nutrition and metabolism, 2017)
Background: In the last 10 years, there has been an increase in the publication of literature dealing with the effects of mild dehydration on cognition in healthy adults. Fewer studies, leading to less consistent data, involved other age groups. Summary: In healthy young adults refraining from drinking or participating in dehydration protocols, it was found that mild dehydration had no impact on performance, whereas the mood was widely impaired. Several studies have also been conducted in young children either as observational studies or as interventional studies. Nevertheless, methodological differences in (de)hydration monitoring, in cognitive assessments, and in the age/brain maturation of study participants, often resulted in contradictory findings regarding the cognitive functions impacted by (de)hydration. Although not consistent, these data showed that not only mood but also performance tend to be impaired by dehydration in children. Even if older adults are likely to be more vulnerable to dehydration than younger adults, very few studies have been conducted in this regard in this population. The results show that, like it is in children, cognition tends to be impaired when the elderly are dehydrated. Taken together, these studies suggest that dehydration has greater detrimental effects in vulnerable populations. Recent imaging data suggest that the brain of children and elderly adults may have fewer resources to manage the effects of dehydration. Consequently, cognitive tasks may be more demanding for younger and older brains and performance more likely to be impaired in these populations, in comparison to young healthy subjects who have greater and more efficient resources.